CULTIVATION OF FILAMENTOUS CYANOBACTERIA FOR VALUABLE BIOPRODUCT USING SAGO SOLID WASTE AS SUBSTRATES - Susanti, Hani; Lestari, Sari; Rahman, Delicia Y.; Susilaningsih, Dwi (Teknologi Indonesia, 2014)
Sago solid waste as by product result of sago palm processing potentially have great value for some bio processing such as source of carbon on microbes substrate. Utilization of sago solid waste as substrate for filamentous cyanobacteria cultivation is a rareresearch activity in Indonesia as one of the three leading world companies producer of sago starch. Therefore, we focused on sago waste treatment using cyanobacteria agent in order to rid the waste and gain the value of nutrition rich starch from that waste. Several concentrations of growth media contain sago solid waste were tested into cyanobacteria culture and solid waste hydrolysis as pretreatment more conducted in the research. Result shows that addition of sago solid waste (50, 500 and 5000 ppm) into media can increase the algae biomass production which is rich of carbohydrate and protein.The proximate value of biomasses with sago solid waste treatment was exhibited significantly higher than control. During cultivation exposure time, the solid waste is gradually consumed by the algae. The study implies that sago solid waste can be used as substrate for the biomass production of filamentous cyanobacteria which is known as source of active compounds, potential resource for valuable bioproduct.